Risk Reporting Practices of Listed Companies: Cross-Country Empirical Evidence from the Auto Industry - Vychytilova, Jana; Nadirov, Orkhan; Pavelkova, Drahomira; Mikeѕka, Martin (Journal of Competitiveness, 2020)
Prior literature has shown that corporate transparency is linked to a firm’s competitiveness. The frequently noted vagueness and inadequacy of reported risk disclosures have been accompanied by calls for industry-specific studies. This paper aims to examine the disclosure informativeness of leading multinational automobile firms worldwide regarding firm-specific risks, namely company risk and company size. Applying a content analysis to examine the prevalent disclosure context in the automotive industry, we analyze and classify the annually reported risk statements of 34 multinationals quoted within the NASDAQ OMX Global Automobile Index. These corporations are headquartered in 10 countries, located in the U.S. as well as in the E.U. and in Asia. Based on an employed Wilcoxon signed rank test, our results show that automobile multinationals favor revealing fewer (more) forward-looking and bad-news risk disclosures as compared to past-looking and good-news risk statements. Our findings further indicate that bigger and riskier automobile multinationals do not reveal larger amounts of risk information. This finding is inconsistent with disclosure theory and provides insight into less complex risk reporting practices that affect investor perceptions of risk by omitting risk information. This paper also provides new empirical evidence regarding the association between company risk and corporate risk disclosing practices in the auto industry; our data show that company size did not play a significant role. With our concentration on explaining current risk reporting practices in the automotive sector, these results are robust with respect to firm-specific risk variables, thus the findings may prove usable for policy frameworks.
Keywords: Risk disclosure.; Content analysis.; Automotive industry.